1999
DOI: 10.1021/es980578x
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Air Contaminants in Porto Alegre, Brazil

Abstract: Information on ambient levels of toxic air contaminants is a critical component of programs aimed at regulating air emissions to protect public health. Yet, this information is not available in many countries. Toxic air contaminants have been measured near a busy highway in downtown Porto Alegre, Brazil, from 3/20/96 to 4/16/97. Of the 42 compounds listed in U.S. EPA Method TO-14, 21 were not detected (concentrations < 0.1 ppb), 3 were detected in only a few samples (CHCl 3 , HClCdCCl 2 , and p-dichlorobenzene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 61 publications
2
49
0
2
Order By: Relevance
“…In other words, 26 and 24 listed compounds were not detected at CW and TW, respectively. A similar study conducted in Porto Alegre, Brazil, in 1997 by Grosjean et al [11] has reported the absence (!0.10 ppbv) of 20 compounds, viz Freon 114, chloroethene, bromomethane, chloroethane, 1,1-dichloroethene, Freon 113, 1,1-dichloroethane, cis-1,2-dichloroethene, 1,2-dichloroethane, 1,2-dichloropropane, cis-1,3-dichloropropene, trans-1,3-dichloropropene, 1,1,2-trichloroethane, 1,2-dibromoethane, chlorobenzene, 1,1,2,2-tetrachloroethane, m-dichlorobenzene, o-dichlorobenzene, 1,2,4-trichlorobenzene and hexachlorobutadiene in urban locations. These 20 compounds were also not detected at the two urban sites in Hong Kong.…”
Section: Resultsmentioning
confidence: 72%
“…In other words, 26 and 24 listed compounds were not detected at CW and TW, respectively. A similar study conducted in Porto Alegre, Brazil, in 1997 by Grosjean et al [11] has reported the absence (!0.10 ppbv) of 20 compounds, viz Freon 114, chloroethene, bromomethane, chloroethane, 1,1-dichloroethene, Freon 113, 1,1-dichloroethane, cis-1,2-dichloroethene, 1,2-dichloroethane, 1,2-dichloropropane, cis-1,3-dichloropropene, trans-1,3-dichloropropene, 1,1,2-trichloroethane, 1,2-dibromoethane, chlorobenzene, 1,1,2,2-tetrachloroethane, m-dichlorobenzene, o-dichlorobenzene, 1,2,4-trichlorobenzene and hexachlorobutadiene in urban locations. These 20 compounds were also not detected at the two urban sites in Hong Kong.…”
Section: Resultsmentioning
confidence: 72%
“…According to the hypothesis of Grosjean et al [20], the generation of SOA only occurs in the daytime (08:00-17:00). The FVOCr and FAC in Equations (2) and (3) were from a smog chamber experiment [20][21][22].…”
Section: Calculation Of Secondary Organic Aerosol Formation Potentialmentioning
confidence: 99%
“…This indicated that the ambient air was mainly impacted by fresh emission sources in winter and by distant sources in spring, summer and autumn. Different VOCs species have different photochemical reactivity and the photochemical age can be judged by their ratios [18,22,49,50]. Different types of VOCs in ambient air have varying chemical activities, and photochemical age of an air mass can be estimated using the ratio of VOCs.…”
Section: Ozone Formation Potentialmentioning
confidence: 99%
“…7 Values obtained in this work are in the same range than those previously obtained in Rio de Janeiro and others Brazilian cities later than 1997, when catalytic converters were currently being used. [8][9][10][11][12][13][14][15] A direct comparison of these values is not possible, once the analytical methods of sampling and analysis were different. Also the technological level of engines, fuels, state law restrictions, fleet composition and vehicular flux are different for each city.…”
Section: Discussionmentioning
confidence: 99%